2018
DOI: 10.1016/j.ajpath.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Signaling Protein 3 Deficiency in Myeloid Cells Promotes Retinal Degeneration and Angiogenesis through Arginase-1 Up-Regulation in Experimental Autoimmune Uveoretinitis

Abstract: The suppressor of cytokine signaling protein 3 (SOCS3) critically controls immune cell activation, although its role in macrophage polarization and function remains controversial. Using experimental autoimmune uveoretinitis (EAU) as a model, we show that inflammation-mediated retinal degeneration is exaggerated and retinal angiogenesis is accelerated in mice with SOCS3 deficiency in myeloid cells (LysMSOCS3). At the acute stage of EAU, the population of infiltrating neutrophils was increased and the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…SOCS1 and SOCS3 expression is known to engage in inhibitory signals to mitigate microglial activation and prevent cell toxicity (Kimura et al, ; Baker et al, ; McCormick & Heller, ). Supporting evidence comes from a study where SOCS3 deficiency in myeloid cells exaggerated retinal degeneration and accelerated retinal angiogenesis in a murine model of uveoretinitis (Chen et al, ). In these mice, SOCS3‐deficient retinas demonstrated higher levels of pro‐inflammatory cytokines IL‐1β, TNF‐α, and IFN‐γ as well as angiogenic factors including VEGF‐A.…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%
“…SOCS1 and SOCS3 expression is known to engage in inhibitory signals to mitigate microglial activation and prevent cell toxicity (Kimura et al, ; Baker et al, ; McCormick & Heller, ). Supporting evidence comes from a study where SOCS3 deficiency in myeloid cells exaggerated retinal degeneration and accelerated retinal angiogenesis in a murine model of uveoretinitis (Chen et al, ). In these mice, SOCS3‐deficient retinas demonstrated higher levels of pro‐inflammatory cytokines IL‐1β, TNF‐α, and IFN‐γ as well as angiogenic factors including VEGF‐A.…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%
“…The Socs3 / mice served as WT control. The LysMCre-Socs3 / mice were obtained by crossbreeding Socs3 / mice with LysMCre mice (31). The Cx3cr1 gfp/gfp mice were provided by Steffen Jung (Weizmann Institute of Science, Rehovot, Israel).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that deletion of Socs3 in LysM + cells (LysMCre-Socs3 / ) did not affect microglia in normal conditions, yet enhanced the in ammatory response in the CNS in experimental autoimmune encephalomyelitis and increased demyelination (30). The in ammatory response in experimental autoimmune uveoretinitis was also exaggerated in LysMCre-Socs3 / mice accompanied by severe retinal degeneration and angiogenesis (31). The LysMCre-Socs3 / mice also developed more severe diabetic retinopathy compared with WT mice (32).…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Arg1 is an intracellular enzyme that inhibits the process of angiogenesis and endothelial cell function by modulating the activity of the nitric oxide synthase. 37 Further studies have shown that blocking the IL-12 receptor not only promotes the expression of proinflammatory gene in the hematoma region and hematoma region CD11b+ cells, but also affects the expression of IFN-γ, TNF-α, IL-4 and IL-13. In addition, our study also found that blocking the IL-12 receptor significantly reduced the proportion of the M1 macrophages and increased the proportion of the M2 macrophages in the hematoma area of rats with ICH.…”
Section: Dovepressmentioning
confidence: 99%